Analisis Sub Elemen Akhlak Beragama dalam Pembiasaan Profil Pelajar Pancasila di SDN Demangan 1 Bangkalan - Mahardhiella, Triana Tasha; Puspitasari, Aditya Dyah (Yayasan Arrahman Nahdlatul Wathan, 2024)
This research aims to determine the sub-elements of religious morals in the profile of Pancasila students at UPTD SDN Demangan 1 Bangkalan. This research uses descriptive quantitative. The population of this research is students in grades III and IV. Sampling used nonprobability sampling technique with purposive sampling type. The sample for this research consisted of 177 students. Data collected using a questionnaire. The results of this research show that religious morals form the character profile of Pancasila students in elementary school students, namely the highest number in the sub-element of knowing and loving God Almighty, namely 762 (86.591%). The highest number in the sub-element of understanding religion/belief was 842 (93.636%). The highest number in the Ritual implementation sub-element was 801 (91.023%).